Relationship between hospital ethical climate, critical thinking disposition, and nursing task performance - Seul-Ki Park; Yeo-Won Jeong (BMC Nursing, 2024)
Abstract Background As ethical conflicts increase in the ever-changing healthcare field, nursing task performance, which is the overall ability of a nurse’s professional knowledge, attitude, and skills, is important for patient health and safety, the provision of quality nursing care, and the appropriate resolution of nursing ethical problems. This study aimed to evaluate the mediating effect of critical thinking disposition on the relationship between hospital ethical climate and nursing task performance. Methods A cross-sectional study was conducted. A total of a convenience sample of 200 clinical nurses from two Korean cities were recruited between November and December 2021. Direct questionnaires and online surveys were used to collect the data. The study variables were analyzed using descriptive statistics, correlations, and a model tested using the Hayes PROCESS macro (Model 4) mediation model. Results The mean scores for hospital ethical climate, critical thinking disposition, and nursing task performance were 91.86 ± 11.29, 97.74 ± 10.70, and 138.58 ± 14.95, respectively. Hospital ethical climate and critical thinking disposition were positively correlated with nursing task performance. In the mediation test model, hospital ethical climate was found to be positively and significantly associated with nursing task performance (ß = 0.46, p < .001) with the mediation of critical thinking disposition (ß = 0.70, p < .001). Conclusions Hospital ethical climate and critical thinking disposition may be important determinants of task performance among clinical nurses. Hospital administrators should make efforts to create a more positive ethical climate in hospitals and conduct education and campaigns on a positive hospital ethical climate for hospital staff to improve nurses’ performance.